Optimasi Formula Tepung Komposit Tinggi Protein dan Seng dengan Response Surface Methodology - Christina Mumpuni Erawati; Ardhia Deasy Rosita Dewi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Covid-19 pandemic had limited people’s movement despite the demand to remain productive and maintain good health. Therefore, it was necessary to provide foods which are easy to distribute, durable, nutritious, and easily transformable to increase immunity. This research aims to develop a composite flour (TK) formula with optimal proportion of wheat flour (TT), snakehead fish flour (TIG), pumpkin flour (TBuL), and pumpkin seed flour (TBiL) which then enriched with zinc. The resulting TK is expected to be used as an ingredient for nutritious snacks containing high protein and zinc. The research was conducted in four stages, namely the making of each constituent flour, determining the best formulation with the Response Surface Methodology using Central Composite Design model, characterizing the physicochemical properties of TK and making meatballs, biscuits, and unting-unting from the TK. The three products were tested on experimental animals for their metabolic responses. The optimization of the formula resulted in three optimal formulations, namely formula A, B, and C with the proportion of TT:TIG:TBuL:TBiL respectively as follows 55:20:15:10; 56.65:20:13.35:10; 57.98:20:12.02:10. The most optimal formula of composite flour was formula A with the highest protein (26.12%) and zinc (18.06 mg/kg) content among other formulas. Then, zinc was added into Formula A using microencapsulation, and TK with protein content of 26.74% and zinc of 56.8 mg/kg were obtained. The histopatology observation on experimental animals showed that the three products made from TK did not cause necrosis of the liver or cell infiltration in the kidneys.